Letter from Harold Llewellyn Bassett to Georg Bredig - Bassett, Harold Llewellyn (1913)
Letter from Harold Llewellyn Bassett to Georg Bredig (1868-1944) thanking him and committing to send Bredig one of his papers in return. In 1913 and 1914, H.L. Basset published two notable papers on pigments titled The Flower Pigments of Antirrhinum Majus. II. The Pale Yellow or Ivory Pigment, and The Flower Pigments of Antirrhinum Majus. III. The Red and Magenta Pigments.
Keywords: Bredig, Georg, 1868-1944; Bassett, Harold Llewellyn